The Distinctive Role of Grounded Optimism and Resilience for predicting Burnout and Work Engagement: A study in Professional Caregivers of Older Adults. (May 2022) - Nieto, Ana; Contador, Israel; Palenzuela, David L.; Ruisoto, Pablo; Ramos, Francisco; Fernández-Calvo, Bernardino
Highlights: The lack of perceived personal control was the main explanatory factor of burnout in professional caregivers of older adults. Resilience and optimism, two closely related psychological constructs, showed a distinctive role for promoting work engagement in professional caregivers. No moderations effects were found between the psychological resources (resilience and optimism) and the vulnerability factor (external control) for predicting work engagement and burnout, respectively. Abstract: Background: Resilience and optimism have been proposed as psychological resources which may help to cope better with work demands, preventing negative consequences of stress, whereas external locus of control (ELC) is considered an intra-psychic vulnerability factor associated with increased burnout. Noteworthy, the specific role of these overlapping constructs on the prevention of burnout and promotion of work engagement, respectively, remains unclear. Objective: The main aim of this study was to compare the differential significance of resilience and optimism, joined with ELC, on the prediction of burnout and work engagement. Method: A sample of 265 professional caregivers of dependent older adults was assessed using an extensive standardized protocol. Optimism and ELC were measured using the Palenzuela's Battery of Generalised Expectancies of Control, and the Connor-Davidson Scale was used to estimate resilience. Moreover, the Maslach Burnout Inventory and the Utrecht Work Engagement Scale were used to measure burnout and work engagement, respectively. Different hierarchical regression models were conducted with burnout and work engagement as dependent factors. Results: The results showed that more than half (51%) variance in resilience was accounted by grounded optimism scores. The ELC was the main explanatory factor of burnout, whereas optimism and resilience were the best predictors of work engagement. Finally, even after controlling the effect of resilience, the effect of optimism remained significant for predicting work engagement. Conclusions: These findings support distinctive role resilience and optimism, two closely related psychological constructs, for promoting work engagement and reducing burnout in professional caregivers of older adults.